Neurostimulation device infection control in China and the United States: a comparative analysis using the MCS framework - Qin, Xiaohan; Chen, Lanfang (Frontiers in Neurology, 2026)
Neurostimulation devices, including deep brain stimulation (DBS) and spinal cord stimulation (SCS) systems, have transformed treatment for neurological disorders and chronic pain. However, device-related infections remain a critical challenge with global incidence rates of 3–7%. This narrative review introduces the Mechanism-Clinical-System (MCS) framework to comprehensively evaluate infection control practices in China and the United States, integrating evidence from 2020 to 2025. At the mechanism level, fundamental differences in sterilization technologies—ethylene oxide dominance in the US versus hydrogen peroxide plasma preference in China—create distinct operational profiles, though clinical outcomes appear equivalent. China’s 10-fold higher antibiotic consumption drives elevated antimicrobial resistance (MRSA: 60–75% vs. 40–55%). Clinically, DBS infection rates remain comparable between countries (US: 3.5–6.5%; China: 5.7%), while prolonged antibiotic prophylaxis (5–14 days) persists in China despite evidence supporting 24-h protocols. At the system level, divergent regulatory frameworks—FDA mandatory compliance versus NMPA’s tiered implementation—create fundamental practice variability. Neither healthcare system demonstrates uniform superiority. The US achieves greater standardization through regulatory stringency, while China demonstrates remarkable adaptability and innovation velocity. Evidence-based harmonization strategies—including international registries, standardized surveillance, and antimicrobial stewardship—offer substantial potential to optimize patient safety globally.